Analisis Terjemahan Tarkīb Iḍāfī Surah Muhammad: Taḥlīlu Tarjamati Tarkīb Iḍāfī fī Sūrati Muḥammad - Rizki, Muhamad Mauludi; Fadhilah, Diki Choirul; Edidarmo, Toto (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
The purpose of this study was to reduce errors and provide insight related to the idhaf tarkib contained in Surah Muhammad. The research design used in this study is library research, so this research data is obtained from written literature. The existing data was then analyzed using a descriptive analysis method of Tarkīb Iḍāfī by analyzing the meaning contained in the idhafah. Idhafah is two isim connected by the implied harf jar, the harf jar, which is estimated between the two isim, namely lam, fii, and min. From this study, researchers found 30 Tarkīb Iḍāfī in surah Muhammad verses 1-15. From Tarkīb Iḍāfī it has the meaning of lamiyah 24, the meaning of min / albayaniyah 2, and the meaning of fii / az-zharfiyah 4.